Antiviral immune response against HTLV-1 invalidates T-SPOT.TB® results in patients with HTLV-1-positive rheumatic diseases - Kimura, Masatoshi; Umekita, Kunihiko; Iwao, Chihiro; Kawano, Katsumi; Hashikura, Yuki; Hashiba, Yayoi; Hidaka, Toshihiko; Sugata, Kenji; Satou, Yorifumi; Miyazaki, Taiga (Frontiers in Immunology, 2024)
[Background] T-SPOT.TB®, one of the screening tests for latent tuberculosis infection (LTBI), yields invalid results in human T-cell leukemia virus type 1 (HTLV-1)-positive patients with rheumatoid arthritis. However, the detailed mechanisms behind this invalidation are unclear. Additionally, it remains unclear whether T-SPOT.TB® or QuantiFERON-TB (QFT) is more useful in HTLV-1-positive patients with rheumatic disease (RD). [Method] Of all the HTLV-1-positive RD patients who visited our department between August 2012 and December 2022, 44 patients who were screened using T-SPOT.TB®️ were included in the analysis. QFT testing was performed in 33 of the 44 patients, and the results were compared with T-SPOT.TB®️. Furthermore, we performed a culture experiment mimicking T-SPOT.TB®️ using peripheral blood mononuclear cells (PBMCs) obtained from HTLV-1-positive patients with RD. Additionally, T-cell subsets with autonomous product IFN-γ were analyzed using a flow cytometer. [Results] Of the included patients, 13 (29.5%) were invalid for T-SPOT.TB®️ because of the increased number of negative control spots. The median HTLV-1 proviral load in the invalid group was higher than that in the valid group (2.45 vs. 0.49 copies/100 PBMCs, respectively, p = 0.002). QFT was performed in all 33 patients, including 13 patients who were invalid in T-SPOT.TB®️. The main source of IFN-γ production was CD8+ T-cells in the T-SPOT.TB®️ mimic experiment. Furthermore, Tax-expressing CD4+ T-cells and Tax-specific cytotoxic CD8+ T-cells were more frequently observed in the patients with the invalid results than in patients with valid results. CD4+ T-cell depletion in the T-SPOT.TB®️ mimic experiment reduced the population of IFN-γ producing CD8+ T-cells. [Conclusion] T-SPOT.TB®️ may be invalidated by the interaction between Tax-expressing CD4+ T-cells and cytotoxic CD8+ T-cells. Moreover, HTLV-1-associated immune reactions due to contact between these cells may be unlikely to occur in QFT using whole blood. Therefore, our results reveal the superiority of QFT over T-SPOT.TB®️ as a screening test for LTBI in HTLV-1-positive patients with RD.